An economic assessment of banana genetic improvement and innovation in the Lake Victoria Region of Uganda and Tanzania - Smale, Melinda; Tushemereirwe, Wilbeforce K. (International Food Policy Research Institute, 2007)
This research report highlights findings from a set of studies applied economists have undertaken on the impact that improved banana cultivars and management practices have had on farmers in the Lake Victoria region of Tanzania and Uganda. A particular focus is on the impact of genetically transformed cooking bananas. Genetic transformation to achieve pest and disease resistance is a promising strategy for smallholder farmers in this region: biotic constraints are severe there and not easily addressed through conventional breeding or control methods. Moreover, exports to world markets are currently negligible, so the risks of reduced exports because of policies against genetically modified foods are low. The crop’s status as both an important food source and significant generator of rural income means that improving productivity could have major social and economic benefits.